2007
DOI: 10.1002/ibd.20234
|View full text |Cite
|
Sign up to set email alerts
|

Changes of OPG and RANKL concentrations in Crohnʼs disease after infliximab therapy

Abstract: IFX therapy decreased the OPG concentration in CD patients significantly. In parallel, the serum bone resorption marker (bCL) also decreased. Concentrations of bone formation marker (OC) and sRANKL increased during the same period; however, those changes were not statistically significant. Elevated OPG in CD could be a counter-regulatory response to inflammatory cytokines or may reflect T-cell activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…The role of TNF-␣ in mediating bone loss is supported by several clinical studies in which IBD patients were treated with infliximab, and markers of bone remodeling were assessed. In these studies, improvements in bone metabolism were observed in the infliximab-treated patients (1,22,43). However, this does not prove that TNF-␣ is the direct cause because TNF-␣ has multiorgan effects.…”
Section: Discussionmentioning
confidence: 92%
“…The role of TNF-␣ in mediating bone loss is supported by several clinical studies in which IBD patients were treated with infliximab, and markers of bone remodeling were assessed. In these studies, improvements in bone metabolism were observed in the infliximab-treated patients (1,22,43). However, this does not prove that TNF-␣ is the direct cause because TNF-␣ has multiorgan effects.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, administration of anti-TNFs has been associated with improved bone mineral density in CD. Long-term maintenance therapy improves bone density and IFX improves bone mineral metabolism in CD [40,41]. …”
Section: Osteoporosis and Osteopeniamentioning
confidence: 99%
“…Accelerated bone resorption - so-called uncoupling - is responsible for low bone mass in CD [32]. It has been demonstrated that serum markers for bone formation and bone resorption are higher in CD than HC [33].…”
Section: Discussionmentioning
confidence: 99%